2013
DOI: 10.1080/10489223.2013.828060
|View full text |Cite
|
Sign up to set email alerts
|

Collectivity, Distributivity, and the Interpretation of Plural Numerical Expressions in Child and Adult Language

Abstract: Sentences containing plural numerical expressions (e.g., two boys) can give rise to two interpretations (collective and distributive), arising from the fact that their representation admits of a part-whole structure. We present the results of a series of experiments designed to explore children’s understanding of this distinction and its implications for the acquisition of linguistic expressions with number words. We show that preschoolers access both interpretations, indicating that they have the requisite li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 71 publications
7
42
2
2
Order By: Relevance
“…The results found for Yudja children were consistent with the results found in previous studies in other languages (BROOKS;BRAINE, 1996, PAGLIARINI et al, 2012SYRETT;MUSSOLINO, 2013) where children favor a distributive interpretation over a collective interpretation in preference tasks, even for sentences without overt markers of distributivity. This was clear in Study 1 where we found a significant age effect.…”
Section: Final Considerationssupporting
confidence: 82%
See 1 more Smart Citation
“…The results found for Yudja children were consistent with the results found in previous studies in other languages (BROOKS;BRAINE, 1996, PAGLIARINI et al, 2012SYRETT;MUSSOLINO, 2013) where children favor a distributive interpretation over a collective interpretation in preference tasks, even for sentences without overt markers of distributivity. This was clear in Study 1 where we found a significant age effect.…”
Section: Final Considerationssupporting
confidence: 82%
“…Acquisition studies present a different pattern, as distributive interpretations are not necessarily dispreferred for children (cf. PAGLIARINI et al, 2012;SYRETT;MUSSOLINO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this is precisely what Syrett & Musolino (2013) found: while adults appear to only allow the collective reading for sentences like (2), children allow both the collective and the distributive readings. While this pattern might appear on the surface to indicate that children overgenerate readings for this sentence relative to adults, we argue instead that children are driven by the semantics, but fail to recruit pragmatic information to constrain the readings to the ones intended in a given context.…”
Section: Introductionsupporting
confidence: 76%
“…To resolve these issues, we begin by turning to previous work reported by Syrett & Musolino (2013). There, participants – both preschoolers and adults – were tested for their understanding of sentences such as the one in (1) and (6a-b) below.…”
Section: The Acquisition Puzzlementioning
confidence: 99%
See 1 more Smart Citation